GENDER AND DEVELOPMMENT OF RAG PICKERS: A CASE STUDY IN PUDUCHERRY (International Journal of Food and Nutritional Sciences, 2022)
The world has change into modernization however changes in the modernization that will concive higher solid waste generation because of the living condition and habituation of the human, consumption behavior of the consumer are changing day by day. The rapid growth rates of the cities combined with their huge population base has left many Indian cities lacking in basic infrastructural facilities like water supply, sanitation and sewerage and solid waste management. In the solid waste management practice are also inadequate in the developed, developing and semi developing countries. The rag pickers plays vital role in the solid waste management practice. They may collect scrap waste from various place and sell to the scraps dealers and the scrap dealers are selling the bulk waste of scrap to the recycling industry. The male and female rag pickers are came out from the families because of financial crisis, family problem. However the countries or cities was developed but still this people are suffering and facing the many problem and the society are also not treated well. This community are not developed still facing the problem like sexual harassment, injury, health issues because of working condition, Dog bite etc., the rag pickers are comes under the informal waste collection and the door to door collector will come under the formal waste collector because of working in the private contract basis, shops but the rag pickers don’t have proper place and time to work. However the world, countries was modernized but the rag pickers livelihood was not changed so the present paper mainly focus on assess the socio-economic condition of rag pickers, gender gap, discrimination of the rag pickers both male and female, standard of living, health aliment of the rag pickers and door to door collector. The study was carried out Puducherry city. still with the problem facing by rag pickers, to show of gender engage in the rag picking and suggest the best option for their standard of living is focused in this paper.